Using of 6% hydroxyethyl starch 130/0.42 in term neonates during acute period of hie. - D. Surkov (Pediatric Anesthesia and Critical Care Journal, 2019)
Introduction Objective of the study is to determine the efficacy of 6% hydroxyethyl starch (HES) 130/0.42 in a balanced crys- talloid solution in term neonates with severe hypoxic-is- chemic encephalopathy. Material and methods Single-center, prospective, simple, randomized con- trolled study was performed in 205 full-term infants with hypoxic-ischemic encephalopathy grade II and grade III by Sarnat score in the period of 2012-2016. Depending on fluids for volume resuscitation, all infants were ran- domly divided into HES and control groups. In HES group 45 term infants with moderate to severe hypoxic-ischemic encephalopathy were treated at the 1st DOL with 6% hydroxyethyl starch (HES) 130/0.42 in a balanced crystalloid solution at a dose of 10 ml/kg. The control group included 160 term neonates with hypoxic- ischemic encephalopathy undergoing routine intensive care with normal saline at a dose of 20 ml/kg as the load- ing volume if needed. To assess the impact of 6% HES on systemic and cerebral hemodynamics, such criteria as mean blood pressure (MBP) and transfontanel Doppler indices RI, PI and CPP were obtained at the 1st, 2nd and 3rd DOL. Results Using of 6% HES 130/0.42 at the dose of 10 ml/kg of body weight for volume replacement in neonates with moderate to severe HIE at the 1st DOL led to increasing of Resistive Index (RI) in front cerebral artery 2nd DOL (p = 0.025) and 3rd DOL (p = 0.023). Conclusions Administration of 6% HES 130/0.42 in term newborns with severe hypoxic-ischemic encephalopathy for vol- ume resuscitation results in significant improvement of cerebral blood flow, specifically increasing of Doppler Resistive Index in front cerebral arteries.